Empowering Women Leading the Green Tourism Revolution in Balikpapan - Andrilla, Riska; Pangemanan, Cindy (Yayasan Sinergi Kawula Muda, 2025)
This paper explores the position of women in the leading green tourism initiatives in Balikpapan, Indonesia, an eco-tourism hot spot confronting rigorous environmental issues and possibilities in sustainable development. The research examines the unique roles and difficulties in green tourism, focusing on their impact on environmental stewardship and community-driven sustainable practices. The main research question is How are women involved in and what barriers do they face towards sustainable tourism in Balikpapan? This research is novel in showcasing the singular power of women in a male-dominated industry and a call for gender-inclusive tourism development policies, a philosophy yet to be treated in the existing literature. Based on the qualitative case study method, this research was based on qualitative interviews conducted with five essential government, environment, and tourism informants’ sectors. Research shows that women are deeply involved in doing business sustainably to promote sustainable tourism, where cultural practices and traditional knowledge face ongoing cultural barriers and limited access to resources. Conclusions highlight the importance of gender-specific support, listing conducting initiatives to accommodate women, such as dedicated training in this field. The study demonstrates that helping how can women's leadership in green tourism promote sustainability development in Balikpapan as a model for other regions.